2019
DOI: 10.1080/25726641.2019.1688904
|View full text |Cite
|
Sign up to set email alerts
|

Modelling copper smelting – the flash smelting plant, process and equipment

Abstract: The effectivity of present copper smelting technologies have their roots in industrial and laboratoryscale experience accumulated over the past decades. Since early '60s, the tools for improving the processing conditions and smelting vessel design included scale modelling and manual computing of homogeneous multicomponent equilibria. The scale models were isothermal, room temperature constructions where water or air was used as medium and dimensionless numbers ensured scale down and scale up similarities. Toda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…The distribution coefficients of copper, iron, and sulfur between matte and slag were calculated using the following Eq. [3]: where [wt pct Me] and (wt pct Me) refer to the experimentally measured elemental concentrations in matte and slag, respectively. The distribution coefficients of elements investigated are displayed in Figure 6 as a function of matte grade.…”
Section: Distributions Of Copper Iron and Sulfur Between Matte Amentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution coefficients of copper, iron, and sulfur between matte and slag were calculated using the following Eq. [3]: where [wt pct Me] and (wt pct Me) refer to the experimentally measured elemental concentrations in matte and slag, respectively. The distribution coefficients of elements investigated are displayed in Figure 6 as a function of matte grade.…”
Section: Distributions Of Copper Iron and Sulfur Between Matte Amentioning
confidence: 99%
“…COPPER flash smelting has been the leading technology for primary copper sulfide smelting [1] because of its low energy consumption and environmental impact, reduced operational costs, and high on-line availability. [2,3] The P SO 2 , generated by the slag and matte formation reactions, in the horizontal settler of the flash smelting furnace (FSF) is equal to the prevailing total pressure. [4,5] Since the late 1970s, the smelting capacity of the FSF has been increased by 100 to 200 pct since technical oxygen (> 95 pct O 2 ) was adopted into copper smelting, [2,6] resulting in increased SO 2 content of the off-gas to > 50 vol pct SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Many industrial applications have been improved over the years thanks to the use of computational fluid dynamics (CFD), a technique that helps to significantly improve process design capabilities. Industrial drying processes [1] are among the applications that benefit from CFD, and many kinetic models have been developed [2]. The adaptability of CFD allows different flow processes to be modeled.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in modeling development has been seen since the introduction of commercially available computational fluid dynamics (CFD) software. The development of the Outotec flash smelting furnace (FSF) and process modeling has been reviewed in a recent review paper [23]. The aim of the modeling studies reported here is to find a feasible computational method by using commercial simulation software packages for gaining a better understanding of the fluid dynamics of the settling matte droplets in the slag layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the geometries and phenomena in the models are computationally extremely intensive, the additional features have to be included one by one as a longer-term target. Finally, the models and knowledge developed will be used to help find ways to reduce copper losses and develop processes and their operational efficiency in a similar manner as has been done with the FS reaction shaft models [23]. In this paper, the fluid dynamics modeling results are presented, and the results obtained with the two software packages are compared.…”
Section: Introductionmentioning
confidence: 99%